Wireless Sensor Networks through Clustering in Cross Layer Network - John, Neethu Maria; Kurian, Simy Mary; Vinodh P, Vijayan; George, Neema (International Journal of Computer Sciences and Engineering, 2025)
One of the significant justification for execution corruption in Wireless sensor network is the upward because of control bundle and parcel conveyance debasement. Clustering in cross layer network operation is an effective way oversee control parcel upward and which at last work on the lifetime of the network. All these overheads are essential in an adaptable networks. The clustering generally experience cluster head failure which need to be solved effectively in a large network. As the center is to work on the normal lifetime of sensor network the cluster head is chosen in view of the battery duration of nodes. The cross-layer activity model optimize the overheads in numerous layer and at last the utilization of bunching will decrease the significant overheads recognized and their by the energy utilization and throughput of remote sensor network is gotten to the next level. The proposed model works on two layers of organization ie., Network Layer and Transport Layer and Clustering is applied in the network layer.